Constitutional and International-Legal Dimensions of Patient Autonomy in the Practice of the Supreme Court of Argentina - Lytvynenko, Anatoliy A.; Machovenko, Jevgenij (Teisė, 2025)
The protection of patients’ rights in the States of Latin America is rapidly emerging in the last decades both in legislation and in case law. In many court judgments originating from Latin America, patients’ rights are very closely tied with constitutional rights of citizens, such as the right to liberty, dignity, inviolability of the person, autonomy and privacy. In this article, the authors explore the relevant case law of the Supreme Court of Argentina, which handed down several influential judgments relating to patient autonomy, mainly relating to the patient’s self-determination, as well as a notorious 2015 judgment affirming the legitimacy of withdrawal of life-supporting treatment of a patient in a permanent vegetative state. The authors explore how the Court interprets the provisions of the Constitution of Argentina in relation to the protection of patient autonomy, as well as the application of the international standards of healthcare enshrined in international legal human rights covenants.